2011
DOI: 10.1007/s00026-011-0114-5
|View full text |Cite
|
Sign up to set email alerts
|

On Noncrossing and Nonnesting Partitions of Type D

Abstract: Abstract. We present an explicit bijection between noncrossing and nonnesting partitions of Coxeter systems of type D which preserves openers, closers and transients. OverviewThe lattice of set partitions of a set of n elements can be interpreted as the intersection lattice for the hyperplane arragement corresponding to a root system of type A n−1 , i.e. the symmetric group of n objects, S n . In particular, two of its subposets are very wellbehaved and widely studied, i.e. the lattice of, respectively, noncro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…[2,12,13,43], so it is quite natural to ask for a generalization of our results to Weyl groups of type B and D.…”
Section: Open Problemsmentioning
confidence: 95%
See 3 more Smart Citations
“…[2,12,13,43], so it is quite natural to ask for a generalization of our results to Weyl groups of type B and D.…”
Section: Open Problemsmentioning
confidence: 95%
“…There are several bijections between noncrossing and nonnesting set partitions (see, for example [2,13,17,29,45]), and since in [19] a Gray code for noncrossing partitions is presented, it is tempting to try employing these bijections in order to obtain a Gray code for nonnesting partitions. But, as referred in [48], a Gray code for a combinatorial class is intrinsically bound to the representation of objects in the class, and in the present case, the Gray code is not preserved under bijection.…”
Section: Preliminaries and Notationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, they showed that their bijections are the unique ones preserving those statistics. There are other bijections between noncrossing and nonnesting partitions of classical types due to Rubey and Stump [18] for type B and Conflitti and Mamede [8] for type D. However their bijections preserve not the types but 'openers' and 'closers'.…”
Section: Rearranging Nonnested Blocksmentioning
confidence: 98%